Periferias na cidade de São Paulo: o caso do Jardim Ângela e do Jardim Riviera - Mendes, Eliston Antonio (2011)
This study examined the question of territory / territoriality and its relationship with power, the state and crime, which arises as part of the power in the suburbs. Through a case study in the districts of Jardim Angela & Jardim Riviera, we consider the socioeconomic factors to reflect on the contradictions in the suburbs today. Presents reports and discussions on educational issues, cultural and leisure activities in the districts in question, so leave the banks to think more broadly in these themes. To validate the considerations of the case study, we examine more specific questions about the ordering of the periphery. These are topics such as condominiums, the logic of capital, the role of social classes and an approach in the slums because they are important components of contemporary urban education. It presents also specific look on the geographical history of the Metropolitan Region, in order to understand the formation of the suburbs nowadays and also the implications of growth of the city and the Metropolitan Region. Thus, to explain some processes that have occurred since the last decades of the nineteenth century until the 1990